Pengaruh Sistem Pengendalian Intern Berdasarkan Coso Framework Terhadap Persediaan Bahan Baku - Herni Syahara; Muhamad Nur Afif; Saeful Anwar (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The objectives to be obtained in this research are to find out the following things: The control environment partially affects the internal control of raw material inventory, Risk assessment partially affects the internal control of raw material inventory, Control activities partially affects the internal control of raw material inventory, Information communication partially affects the internal control of raw material inventory, Monitoring partially affects the internal control of raw material inventory. Control environment, risk assessment, control activities, information communication and monitoring simultaneously influences internal control of inventory raw materials. The samples in this research were 86 people who were all employees of the warehouse department related to the internal control system for inventory at PT. Yongjin Javasuka Garment Sukabumi. The analytical method used is multiple regression analysis. The results show that the control environment, risk assessment, control activities, information communication and monitoring partially or simultaneously affect the internal control of raw material inventory at PT. Yongjin Javasuka Garment Sukabumi.